2016
DOI: 10.1007/s10549-016-3853-5
|View full text |Cite
|
Sign up to set email alerts
|

Stromal cells in phyllodes tumors of the breast are enriched for EZH2 and stem cell marker expression

Abstract: Phyllodes tumors (PTs) of the breast are fibroepithelial neoplasms with stromal hypercellularity, which is the basis for their classification as benign, borderline, and malignant. The histologic diagnosis of PTs is often difficult, and the pathological features may not always predict clinical behavior. The pathobiology of PT remains poorly understood. Enhancer of Zeste 2 (EZH2) epigenetically regulates cell-type identity, cellular differentiation, and breast cancer stem cells. EZH2 exerts oncogenic functions i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 39 publications
3
6
0
Order By: Relevance
“…Once exposed to CAF‐like Stroma tA cells, or so‐called ‘reactive stroma’, EPs may have been further stimulated and underwent a mesenchymal transition. Previous studies have reported the expression of stem cell markers in the stroma 36,37 . In the present study, we observed that TEP cells expressed both EPs and mesenchymal markers, providing evidence of the presence of less differentiated cells in the stroma.…”
Section: Discussionsupporting
confidence: 79%
“…Once exposed to CAF‐like Stroma tA cells, or so‐called ‘reactive stroma’, EPs may have been further stimulated and underwent a mesenchymal transition. Previous studies have reported the expression of stem cell markers in the stroma 36,37 . In the present study, we observed that TEP cells expressed both EPs and mesenchymal markers, providing evidence of the presence of less differentiated cells in the stroma.…”
Section: Discussionsupporting
confidence: 79%
“…Our study results for PT were similar to the study reported by Zhang et al . that EZH2 expression was directly correlated with stromal cellularity, nuclear atypia, and the number of mitoses, as well as the overall grade of tumors 5 . Frequent high EZH2 expression in MBC with spindle cell features was also reported previously 4 .…”
Section: Discussionsupporting
confidence: 65%
“…Enhancer of zeste homolog 2 (EZH2) overexpression was demonstrated in various cancer types, including breast cancer, in which high EZH2 expression is associated with adverse clinicopathologic features and aggressive behavior 3 . Moreover, malignant phyllodes tumor (PT) and metaplastic breast carcinoma (MBC) with spindle cell morphology were also reported to overexpress EZH2 in previous studies 4,5 …”
Section: Introductionmentioning
confidence: 98%
“…Recently, a role of histone methylation of TERT regulation has been demonstrated 24 . Of interest, stromal EZH2, an epigenetic modifier, was significantly associated with PT malignancy 25 . Additionally, TERT gene amplification was only reported in malignant PTs 7 .…”
Section: Discussionmentioning
confidence: 99%